Penggunaan Media Animasi pada Kompetensi Memahami Dasar-Dasar Sistem Hidraulik Siswa SMK Teknik dan Bisnis Sepeda Motor - Fritman Dalito; Wiyogo Wiyogo; Jhonni Rentas Duling (Jurnal Taman Vokasi, 2019)
Abstracts. This study aims to: Determine the effect of the use of animation media on the competence to understand the basics of hydraulic systems to improve student learning outcomes in class X Engineering and Business of Motorcycle Bikes at SMK Negeri 1 Palangka Raya. The population in the study applied was all students of class X Motor in SMK 1 Palangka Raya second semester Academic Year 2018/2019. The research sample chosen was class X Engineering and Motorbike Business with students totaling 31 students. The instruments applied in this study are: observation sheets of teacher and student activities, questionnaire sheets of student responses to the use of animation media on learning and student learning outcomes tests. Based on the results of research conducted with the use of animation media in Competence Basics of Hydraulic Systems in class X Engineering and Motorcycle Business, has an influence on student learning outcomes, where the level of achievement in learning with the use of animation media is 89.4% with very achievable information because there are at the percentage of 80% -100%, and the completeness of student learning in classical is at the percentage of 87%, so it can also be declared very complete.